Pengaruh Fasilitas Kerja terhadap Kinerja Karyawan pada Cv. Asla Jambi - Aulia Balqis (Science of Management and Students Research Journal (SMS), 2021)
The purpose of this study was to determine and describe the work facilities and employee performance of CV. ASLA Jambi, to determine and analyze the effect of work facilities on the performance of employees of CV. ASLA Jambi. The benefits of this research provide additional information for interested parties in the industrial world about work facilities that have to do with employee performance so that efforts can be made to maintain work facilities that can improve work for employees. The research method uses descriptive analysis methods with library research, field research, and Questionnaires. The location of this company is at Jl. Abdul Rahman Saleh No. 57 Rt.09/03 Ex. Old Red Paal Kec. South Jambi. Company CV. Anugrah Sinar Laut Abadi (ASLA). The results show that the t-count value is 4.627 calculations using the SPSS program while the t-table is 2.034 with a significant level of 5%, df (32) from the t-distribution table. Shows that the t-count value is greater than the t-table (t-count t-table ) 4.627 2.034. This shows that work facilities have an influence on employee performance at CV.ASLA Jambi. So that Ho is rejected and H1 is accepted. It is hoped that CV. ASLA Jambi will pay attention to facilities, especially machines and equipment that are not sufficient or incomplete in order to support employee work processes and have an impact on work results.